2015
DOI: 10.1002/ange.201509071
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Mode Controlled Self‐Assembly of TiO2 Nanoparticles Through a Cucurbit[8]uril‐Enhanced Radical Cation Dimerization Interaction

Abstract: The realization of controllable multicomponent selfassembly through reversible supramolecular interactions is ac hallenging goal, and is an important strategy for the fabrication of switchablen anomaterials.H erein we showt hat the self-assembly of TiO 2 nanoparticles (NP) functionalized with methyl viologen can be controlled both by light irradiation and chemical reduction through cucurbit[8]uril-enhanced radical cation dimerization interactions.M oreover,t he controlled assembly and disassembly of this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Our previous work showed that the controllably antibacterial activity of CPs could be realized by host−guest interaction of cucurbit [7]uril (CB [7]) and amantadine (AD), 34 also photocatalytic activity could be controlled by the assembly and disassembly of cucurbit [8]uril (CB [8]) and MV 2+ anchored on the titanium dioxide (TiO 2 ) nanoparticles. 35 The supramolecular assembly and dis-assembly processes of MV 2+ and cucurbit [8]uril (CB [8]) was further used to reversibly "turn-on" and "turnoff" hydrogen generation of the polymer system.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that the controllably antibacterial activity of CPs could be realized by host−guest interaction of cucurbit [7]uril (CB [7]) and amantadine (AD), 34 also photocatalytic activity could be controlled by the assembly and disassembly of cucurbit [8]uril (CB [8]) and MV 2+ anchored on the titanium dioxide (TiO 2 ) nanoparticles. 35 The supramolecular assembly and dis-assembly processes of MV 2+ and cucurbit [8]uril (CB [8]) was further used to reversibly "turn-on" and "turnoff" hydrogen generation of the polymer system.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐assembly of supramolecular polymers is a powerful tool for producing functional materials that combine several properties and may respond to external conditions . Recently, the construction of coordination supramolecular or coordination polymers has emerged as a powerful and versatile strategy for engineering metallo‐polymers .…”
Section: Introductionmentioning
confidence: 99%